ANALISIS JAWABAN SISWA DALAM KEMAMPUAN LITERASI NUMERASI MATEMATIS SISWA SMP - Hotma Fifia Lubis; Friska Ledina Situngkir (JURNAL ILMIAH NUSANTARA, 2026)
This study aims to analyze students' answers regarding their mathematical numeracy literacy skills on the topic of ratio and proportion among seventh-grade students of SMP Budi Murni 2 Medan in the 2025/2026 academic year. This research employed a descriptive qualitative approach in the form of a mini research, involving 30 seventh-grade students selected through purposive sampling. Data were collected through a written test consisting of four numeracy literacy essay questions on ratio and proportion, covering cognitive levels C4 (analyzing), C5 (evaluating), and C6 (creating), followed by semi-structured interviews. Data were analyzed using the Miles and Huberman model, with technique triangulation to ensure validity. The results showed that students' numeracy literacy skills remained low, with only 7 students (23.3%) achieving scores above the minimum learning completion criteria (KKTP), while 23 students (76.7%) scored below it. Based on indicator analysis, the lowest achievement was found in the indicator of communicating and concluding results (very low), followed by analyzing information and applying appropriate mathematical concepts and procedures (low), while the indicator of understanding the problem was categorized as moderate. Three main error patterns were identified: conceptual errors in understanding ratio as a part-whole relationship, procedural errors in applying solution steps, and communicative errors in formulating logical and systematic conclusions. These findings indicate the need for more contextual and student-centered learning innovations, such as Problem Based Learning (PBL), to improve junior high school students' numeracy literacy skills in the topic of ratio and proportion.